Cost- Effective Methods and Devices for home scale adoption of Plant Tissue Culture - Deepa V (Department of Horticulture, College of Agriculture, 1996)
Attempts were made to develop cost-effective methods and devices for home scale adoption of plant tissue culture in the plant tissue culture laboratory of the Department of Horticulture, College of Agriculture, Vellayani, during 1993-95. The test plant selected for the study was Anthurium andreanum Lind. (Pink). Segments of leaf were used as explant for cullus initiation. The callus so obtained was used for further regeneration studies. Various low cost equipment were fabricated and tested for their efficiency in comparison to the conventional expensive method. One-fourth strength of the major nutrients of MS medium along with full strength of micro nutrients was found good for the induction of multiple shoots. All the growth parameters were found adversely affected by the use of LR grade chemicals, when compared to AR grade chemicals. Confectionary grade sugar was found to be equally good to AR grade sucrose, while commercial grade crystal sugar was not. Rain water could be used as a substitute to double glass distilled water in the culture medium. Attempts to substitute agar-agar with less expensive playing marbles, as support matrix of the culture medium was also successful. Ordinary (gold-smith type) balance could be used to replace the expensive electronic balance in weighing chemicals for media preparation. The pH indicator paper could be effectively used